Managing strategic reorientation of new ventures in a developing country context - Şen, Anıl (Graduate School, 2023)
New ventures often undergo strategic reorientations while searching for a market fit. They target establishing and maintaining their legitimacy among specific audiences. However, these moves may limit their legitimacy in their further moves. In explaining how actors justify fundamental strategy redirections, the research identified a sequence of stratagems helping actors change their strategies while showing commitment to earlier objectives to maintain legitimacy while positioning strategic changes in an established institutional environment, like the USA. To shed light on how ventures manage strategic reorientations in a less institutionalized environment, such as a developing country, we performed an inductive, comparative case study of ventures in a nascent financial-technology sector similar to the original study that identified the series of stratagems. Our case studies were compared and constructed among themselves and with the original study in the USA to identify the impacts of contextual differences. The comparisons reveal that these ventures also pursued parallel reorientations in a different contextual environment and produced comparable end products. However, their audiences and their audience management approaches have diverged even further. The developing country context offers unique challenges and opportunities for strategic reorientation. The study also has methodological contributions. While this study was not entirely a replication, it contributes to our understanding of qualitative research in comparable and non-comparable environments. It also discusses theoretical limits and practical opportunities for performing qualitative research with a replicative logic across contexts.
Gelişmekte olan bir pazarda yeni kurulan bir girişimi pivot etmek
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: market; legitimacy; strategic changes